Respuesta :

Answer:

C

Step-by-step explanation:

Given

S = [tex]\frac{C-\frac{1}{4}I }{C+I}[/tex] ( multiply both sides by C + I )

S(C + I) = C - [tex]\frac{1}{4}[/tex] I ← distribute left side

SC + SI = C - [tex]\frac{1}{4}[/tex] I ( multiply through by 4 to clear the fraction )

4SC + 4SI = 4C - I ( add I to both sides )

4SC + 4SI + I = 4C ( subtract 4SC from both sides )

4SI + I = 4C - 4SC ← factor out I from each term on the left side

I(4S + 1) = 4C - 4SC ← factor out 4C from each term on the right side

I(4S + 1) = 4C(1 - 4S) ← divide both sides by (4S + 1)

I = [tex]\frac{4C(1-4S)}{4S+1}[/tex]